Metal-organic frameworks derived reverse-encapsulation Co-NC@Mo2C complex for efficient overall water splitting. (March 2019) - Liang, Qirui; Jin, Huihui; Wang, Zhe; Xiong, Yuli; Yuan, Shuai; Zeng, Xianci; He, Daping; Mu, Shichun
Abstract: Developing low-cost, highly active, and stable bifunctional electrocatalysts is a challenging issue in electrochemical water electrolysis. Herein, we develop a simple metal organic frameworks (MOFs) based approach to prepare bifunctional Co-NC@ Mo2 C complex catalysts. Differently from traditional carbon encapsulated functional nanomaterials, herein the carbon-based framework derived carbonitride and Co nanoparticles (Co-NC) are encapsulated with Mo2 C. Benefiting from the unique reverse-encapsulation structure and synergetic effects of Mo2 C and Co-NC, the Co-NC@Mo2 C catalyst shows superior hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) performance. In alkaline media, it affords the current density of 10 mA cm −2 at low overpotentials of 99 mV and 347 mV for HER and OER, respectively. Interestingly, due to a reversed encapsulation structure where Co nanoparticles are protected by Mo2 C, it leads to an outstanding HER catalytic activity (a low overpotential of 143 mV) and stability in acidic solutions. Remarkably, when employed as both the cathode and anode for overall water splitting, a low cell voltage of 1.685 V is required to reach the current density of 10 mA cm −2 in alkaline media with excellent stability, making the Co-NC@Mo2 C an efficient non noble metal bifunctional electrocatalyst toward water splitting. Graphical abstract: A simple metal organic frameworks based approach to prepare bifunctional Co-NC@Mo2 C complex catalysts with a reverse-encapsulation structure and enhanced catalytic performance. fx1 Highlights: A simple metal organic frameworks (MOFs) based approach is used to prepare bifunctional Co-NC@Mo2 C complex catalysts. The catalyst shows a reverse-encapsulation structure where the carbon-based framework is encapsulated with Mo2 C. Mo2 C protects the electrocatalytic carbon-supported Co NPs and provides more metal active sites.